2022
DOI: 10.1024/1662-9647/a000261
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Late Life

Abstract: Abstract. Personality disorders (PDs) affect a significant portion of older adults and hinder their physical and mental health. This narrative review (1) reviews the literature on PDs in older adults and (2) presents guidelines for clinicians in recognizing and managing this population. The presentation of Cluster A or C patients may remain stable or intensify, while Cluster B patients may shift to subtler presentations. Among assessment instruments, the Hetero-Anamnestic Personality Questionnaire is most prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(131 reference statements)
1
1
0
Order By: Relevance
“…Meta‐regressions also indicated that the associations between ACEs and cluster C personality disorders decreased with sample mean age. This is in line with previous observations that the symptoms of the personality disorders in this cluster seem to decrease throughout adulthood (Skodol et al, 2007; Wright et al, 2011; but see Bangash, 2022; Cruitt & Oltmanns, 2018; Wu & Francois, 2021). In contrast, the percentage of females in the sample did not influence any of the associations investigated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Meta‐regressions also indicated that the associations between ACEs and cluster C personality disorders decreased with sample mean age. This is in line with previous observations that the symptoms of the personality disorders in this cluster seem to decrease throughout adulthood (Skodol et al, 2007; Wright et al, 2011; but see Bangash, 2022; Cruitt & Oltmanns, 2018; Wu & Francois, 2021). In contrast, the percentage of females in the sample did not influence any of the associations investigated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…These may manifest externally through the avoidance of social interactions/situations or internally to avoid experiencing distressing thoughts, feelings, or sensations concerning pain ( 60 ). In addition, a recent review has summarized that features of these disorders tend to be more stable over time ( 61 ), and thus, avoidance styles of coping may became more entrenched and operate in the maintenance of comorbidities.…”
Section: Discussionmentioning
confidence: 99%